Inferring cultural similarity among Brazilian states based on data from social media advertising platforms - Inocêncio Júnior, Ronaldo L.; Ribeiro, Filipe N. (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2020: Proceedings of the 26th Brazilian Symposium on Multimedia and the Web, 2020)
Due to its continental size, Brazil is one of the countries with the largest territorial extension in the world, with a total of 27 federative units, and prominent cultural diversity. Brazil is also among the five countries with the largest social inequality according to the UN, which may stimulate the interstate migration process. This process contributes to an increase in cultural diffusion across the states of origin and destination of migrants since they move with all their habits including food and drink preferences. In our work, we measured the similarity among Brazilian states, analyzing food and drink preferences as a cultural indicator. By leveraging the Facebook advertising platform, which allows us to obtain an estimate of the total number of users who satisfy a set of attributes provided, we collected the audience for food and drinks in Brazil to conduct our analysis. In order to validate our results, we compared the cultural similarity of the states with the rate of migrants they received in a given period. Our results reveal a positive correlation between cultural similarity and the rate of migration.